A Scientometric Analysis and Visualization of Research on Parkinson's Disease Associated With Pesticide Exposure - Liu, Chaoyang; Liu, Zehua; Zhang, Zhentao; Li, Yanan; Fang, Ruying; Li, Fei; Zhang, Jingdong (Frontiers in Public Health, 2020)
The etiology and pathogenesis of Parkinson's disease (PD) have not yet been clearly described. Both genetic and environmental factors contribute to the onset and progression of PD. Some pesticides have been demonstrated to be associated with PD by many previous studies and experiments, and an increasing number of researchers have paid attention to this area in recent years. This paper aims to explore the knowledge structure, analyze the current research hot spots, and discuss the research trend through screening and summarizing the present literature. Based on 1767 articles from the Web of Science core collection and PubMed database, this study carried on the analysis from the keywords, cited references, countries, authors and some other aspects by using Citespace. The hot topics, valuable articles, productive authors in this research field could be found after that. To the best of our knowledge, this is the first study to specifically visualize the relationship between pesticide exposure and PD, and forecast research tendency in the future.